Nighttime Lights as a Proxy for Human Development at the Local Level - Anna Bruederle; Roland Hodler (Center for Economic Studies and ifo Institute (CESifo), 2017)
Nighttime lights are increasingly used by social scientists as a proxy for economic activity and economic development in subnational spatial units. However, so far, our understanding of what nighttime lights capture is limited. We construct local indicators of household wealth, education and health from geo-coded Demographic and Health Surveys (DHS) for 29 African countries. We show that nighttime lights are positively associated with these indicators across DHS cluster locations as well as across grid cells of roughly 50 x 50 km. We conclude that nighttime lights are a good proxy for human development at the local level.
Keywords: I15; I25; I32; O15; O55; 330; nighttime lights; local development; Africa